Jackson College dancers rehearsing, (l to r) Jean Glancy, J1953, Anne Jenkins, A1952, Loris Lakso, J1952, Diana Howard, J1953, Mary Ellen Fitzgerald, J1953, 1951 - Unknown (Tufts Archival Research Center, 2005)
8x10